The Problems of Siri Marriage for Women in Tambang District, Kampar Regency: A Gender Swot Analysis Study - Nelli, Jumni (AL-ISTINBATH : Jurnal Hukum Islam, 2022)
This paper aims to reveal the problems of sirri marriage, and find a solution. Sirri marriages, which are considered religiously valid, have caused many problems that have an impact on women's losses. But there are still many women who are comfortable doing it. This study used a SWOT gender analysis data analysis. The results of this study revealed that in general sirri marriages were carried out for reasons of wanting to obtain religious legitimacy, so as to create inner peace, at least avoiding immoral acts. The basic problems felt by women who do unregistered marriages are psychological problems and mental stress as a result of legal uncertainty about their marital status. Seeing more weaknesses and threats that occur in sirri marriages, then the existing advantages will not be able to overcome the problems faced unless they take advantage of existing opportunities, namely itsbat nikah. According to Islamic marriage law, if the consequences of marriage are known to be strongly suspected of causing harm, then the law is haram. Furthermore, it is necessary to enter registration as a condition for a valid marriage.